At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
x4−x3−6x2+4x+80 is your answer
you want to use grouping to factor this polynomial
for the first 3 terms, you can factor out an X^2
how should i group them?
i got x^2(x^2-x-6)+4(x+2)
x^2(x-3)(x+2)+4(x+2) (x+2)(x^2(x-3)+4) :/
lets start over
x^4 - x^3 - 6x^2 + 4x + 8 = 0
use factor and remainder theorem to solve it
x^2(x^2 - x - 6) + 4(x + 2) = 0
do you have to use special factors?
see by plugging x=-2 the expression x^4 - x^3 - 6x^2 + 4x + 8 becomes 0 hence x+2 is one of the factor for getting other factors divide x^4 - x^3 - 6x^2 + 4x + 8 by x+2
no... (x^2+4)(x-3)(x+2)^2=0 now solve each equal to zero
no to special factors, matricked is right also
how'd you get there..
x=-2 and x=2 x=3
you skipped a couple steps from x^2(x^2 - x - 6) + 4(x + 2) = 0
i further factored (x^2-x-6) and grouped (x^2+4)
can you show me how, from there, you got (x^2+4)(x-3)(x+2)^2=0?
now set each equation equal to 0
the x^2 and +4 you pulled out go in their own equation
wait so from x^2(x-3)(x+2) + 4(x+2) = (x^2+4)(x+2)^2 (x-3)?
now set each equal to zero by themselves and solve for x
the rest i know how, but h\where's the logic in that move, where you can take x^2+4
you factored it out by grouping
it is my understanding that in order to factor by grouping both pieces need to have common factors like, "4(x+2)" doesn't have a (x-3)
are you learning imaginary numbers?
right, but x^2-x-6 did
you further factored
x^4 - x^3 - 6x^2 + 4x + 8=0 x^4 +2x^3 -3x^3 - 6x^2 + 4x + 8=0 X^3(x+2) -3x^2(x+2) +4(x+2)=0 (x+2)(x^3-3x^2+4)=0 (x+2)(x^3-2x^2-x^2+4)=0 (x+2)(x^2(x-2) - (x+2)(x-2))=0 (x+2)(x-2)(x^2-x-2)=0 (x+2)(x-2)(x^2-2x+x-2)=0 (x+2)(x-2)(x(x-2)+1(x-2))=0 or(x+2)(x-2)(x-2)(x+1)=0 now set each equal to 0 thus the roots are -1,-2,2,2
wow, nice job